NONLINEAR ANALYSES OF PARTIALLY COMPOSITE STEEL BEAMS ENCASED IN CONCRETE WITH INNOVATIVE POSITION OF STUD BOLTS (Journal of Engineering, 2009)
Static behavior of three partially encased composite steel beams with cambering under flexural condition is investigated in the context of studying some alternative positions for the headed studs. Shear resistance between the cambered I-shaped beam and the concrete was provided by headed studs in two positions: vertically welded on the bottom flange and horizontally welded on the faces of the web. In the present study, a nonlinear three-dimensional finite element analysis has been used to predict the load-deflection and moment-rotation behaviors of composite encased beams consisting of steel sections using the finite element computer program (ANSYS V. 10). Composite encased beams are analyzed and a comparison ismade with available experimental load-deflection curves, good agreement with the experimental results is observed. Cambering of steel section is introduced on the steel section of the composite beams encased in concrete. It is found that using of steel section with cambering can increase the ultimate load capacity of the composite encased beam by relatively (15%) and also it is found that deflection are nearly (65% to 80%) the deflection of the same beam without cambering. Parametric studies have been carried out to study the increasing of the momentcarrying capacity due to the use of encased concrete; meanwhile the slip along the beams length is studied. The strain distributions along the steel section and encased concrete depth are also examined. The effects of concrete compressive strength on the stiffness of the composite encased beams are also investigated with the Poisson’s ratio of concrete and the effect ofcambering of steel-section.